Replication Data for: Correlation between tectonic stress regimes and methane seepage on the west-Svalbard margin - Plaza-Faverola, Andreia; Keiding, Marie (DataverseNO, 2019)
Seismic and tectonic stress models associated with a publication by Plaza-Faverola and Keiding in Solid Earth (Copernicus open access journal). Abstract: Methane seepage occurs across the west-Svalbard margin at water depths ranging from < 300 m, landward from the shelf break, to > 1000 m in regions just a few kilometres away from the mid-ocean ridges in the Fram Strait. The mechanisms controlling seepage remain elusive. The Vestnesa sedimentary ridge, located on oceanic crust at 1000-1700 m water depth, hosts a perennial gas hydrate and associated free gas system. The restricted occurrence of acoustic flares to the eastern segment of the sedimentary ridge, despite the presence of pockmarks along the entire ridge, indicates a spatial variation in seepage activity. This variation coincides with a change in the faulting pattern as well as in the characteristics of fluid flow features. Due to the position of the Vestnesa ridge with respect to the Molloy and Knipovich mid-ocean ridges, it has been suggested that seepage along the ridge has a tectonic control. We modelled the tectonic stress regime due to oblique spreading along the Molloy and Knipovich ridges to investigate whether spatial variations in the tectonic regime along the Vestnesa Ridge are plausible. The model predicts a zone of tensile stress that extends northward from the Knipovich Ridge and encompasses the zone of acoustic flares on the eastern Vestnesa Ridge. In this zone the orientation of the maximum principal stress is parallel to pre-existing faults. The model predicts a strike-slip stress regime in regions with pockmarks where acoustic flares have not been documented. If a certain degree of coupling is assumed between deep crustal and near-surface deformation, it is possible that ridge push forces have influenced seepage activity in the region by interacting with the pore-pressure regime at the base of the gas hydrate stability zone. More abundant seepage on the eastern Vestnesa Ridge at present may be facilitated by dilation of faults and fractures favourably oriented with respect to the stress field. A modified state of stress in the past, for instance due to more significant glacial stress, may have explained a vigorous seepage activity along the entire Vestnesa Ridge. The contribution of other mechanisms to the state of stress (i.e., sedimentary loading and lithospheric flexure) remain to be investigated. Our study provides a first order assessment of how tectonic stresses may be influencing the kinematics of near-surface faults and associated seepage activity offshore the west-Svalbard margin.